ANALISIS KONDISI METEOROLOGI TERKAIT KEJADIAN KEBAKARAN HUTAN DI LERENG GUNUNG MERBABU - Anendha Destantyo Nugroho; Muhammad Zakky Faza; Paulus Agus Winarso (Universitas Sebelas Maret, 2018)
Abstract:. There was a fire in the land and forest of the Gunung Merbabu National Park in Semarang Regency, Central Java. The fire burned the land on Sunday, October 14 2018 afternoon, the area of land in the forest area of Mount Merbabu which was burned reached 100 hectares. The number is predicted to increase because the flames have not been extinguished. Fires in the Mount Merbabu National Park not only damage the forest ecosystem. The fire also decided the pipeline of clean water flowing to a number of hamlets in Batur Village. Land and forest fires are supported by meteorological drought, so studies need to be done to find out the magnitude of meteorological factors that support forest fires and the extent of burning areas. This research was conducted by analyzing the results of meteorological observations obtained from AWS (Automatic Weather Station) installed not far from the slopes of Mount Merbabu, including AWS Pakem Yogyakarta, AWS Borobudur Magelang, AWS Undip Semarang. In addition to the analysis of surface observation data, this study also analyzes the atmospheric conditions of surface wind maps, Rainy Days, and observations of satellite images during the occurrence of land and forest fires in Mount Merbabu National Park.Abstrak: Terjadi kebakaran lahan dan hutan Taman Nasional Gunung Merbabu di Kabupaten Semarang, Jawa Tengah. Api membakar lahan pada Minggu 14 Oktober 2018 sore, luas lahan di kawasan hutan Gunung Merbabu yang terbakar mencapai 100 hektar. Jumlah itu diprediksi bertambah karena kobaran api belum berhasil dipadamkan. Kebakaran di Taman Nasional Gunung Merbabu tidak hanya merusak ekosistem hutan. Kebakaran juga memutuskan jaringan pipa air bersih yang mengalir ke sejumlah dusun di Desa Batur. Kebakaran lahan dan hutan tersebut didukung oleh faktor kekeringan meteorologi, sehingga perlu dilakukan kajian untuk mengetahui besarnya faktor meteorologi yang mendukung terjadinya kebakaran hutan serta meluasnya area yang terbakar. Penelitian ini dilakukan dengan analisis hasil pengamatan meteorologi yang didapatkan dari AWS (Automatic Weather Station) yang terpasang tidak jauh dari lereng Gunung Merbabu, antara lain AWS Pakem Yogyakarta, AWS Borobudur Magelang, AWS Undip Semarang. Selain analisis dari data hasil pengamatan permukaan, penelitian ini juga melakukan analisis kondisi atmosfer peta angin permukaan, Hari Tanpa Hujan, serta pantauan citra satelit saat terjadinya kebakaran lahan dan hutan di Taman Nasional Gunung Merbabu.